2006
DOI: 10.1186/1471-2474-7-68
|View full text |Cite
|
Sign up to set email alerts
|

Immediate effects of spinal manipulation on thermal pain sensitivity: an experimental study

Abstract: Background: The underlying causes of spinal manipulation hypoalgesia are largely unknown. The beneficial clinical effects were originally theorized to be due to biomechanical changes, but recent research has suggested spinal manipulation may have a direct neurophysiological effect on pain perception through dorsal horn inhibition. This study added to this literature by investigating whether spinal manipulation hypoalgesia was: a) local to anatomical areas innervated by the lumbar spine; b) correlated with psyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
146
2
6

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(162 citation statements)
references
References 62 publications
8
146
2
6
Order By: Relevance
“…Our study found significant between-group mean differences of 8.0 points (16.0%) for disability (NDI) and 2.0 points for pain; likewise, Cleland et al 21 reported between-group mean differences of 5.0 points (10.0%) for disability (NDI) and 2.0 points for pain (NPRS) at 48-hour follow-up. Perhaps the combined effect of both upper cervical and upper thoracic HVLA thrust manipulation, as compared to thoracic HVLA thrust manipulation alone, explains the greater reduction in disability (NDI) found in our study than in that found by Cleland et al 21 In addition, Puentedura et al 80 demonstrated greater reductions in disability at all follow-up points when the HVLA thrust manipulation was directed to the cervical spine rather than the thoracic spine in patients with neck pain; however, the sample size was just 24 patients and, unlike our study, the mean duration of symptoms in the Puentedura et al 80 6 and it is plausible that the clinical benefits found in our study are associated with a neurophysiological response involving temporal sensory summation at the dorsal horn of the spinal cord 3 ; however, this proposed model is currently supported only by findings from transient, experimentally induced pain in healthy subjects [3][4][5]8,34 and not in patients with neck pain. In summary, there is currently insufficient evidence to support a dominant role of any of these 3 hypoalgesic mechanisms.…”
Section: Discussioncontrasting
confidence: 50%
“…Our study found significant between-group mean differences of 8.0 points (16.0%) for disability (NDI) and 2.0 points for pain; likewise, Cleland et al 21 reported between-group mean differences of 5.0 points (10.0%) for disability (NDI) and 2.0 points for pain (NPRS) at 48-hour follow-up. Perhaps the combined effect of both upper cervical and upper thoracic HVLA thrust manipulation, as compared to thoracic HVLA thrust manipulation alone, explains the greater reduction in disability (NDI) found in our study than in that found by Cleland et al 21 In addition, Puentedura et al 80 demonstrated greater reductions in disability at all follow-up points when the HVLA thrust manipulation was directed to the cervical spine rather than the thoracic spine in patients with neck pain; however, the sample size was just 24 patients and, unlike our study, the mean duration of symptoms in the Puentedura et al 80 6 and it is plausible that the clinical benefits found in our study are associated with a neurophysiological response involving temporal sensory summation at the dorsal horn of the spinal cord 3 ; however, this proposed model is currently supported only by findings from transient, experimentally induced pain in healthy subjects [3][4][5]8,34 and not in patients with neck pain. In summary, there is currently insufficient evidence to support a dominant role of any of these 3 hypoalgesic mechanisms.…”
Section: Discussioncontrasting
confidence: 50%
“…13,24 Collectively, these studies suggest that spinal manipulative therapy has a direct effect on the central nervous system. This means that clinical outcomes associated with spinal manipulative therapy may result from multiple neurophysiological mechanisms working alone or in combination.…”
Section: What Should Be the Response?mentioning
confidence: 99%
“…In contrast, more recent evidence tends to favor a neurophysiologic mechanism of action for spinal manipulation. 4,22,25,26,37,40 Several researchers have identified neurophysiologic changes to include altered motor neuron pool excitability, 10,17,26,39 hypoalgesia, 21,45,50 and increased sympathetic nervous system activity 45,50,51 following spinal manipulation. The facilitation or disinhibition of neural pathways associated with manipulation has been suggested as a possible mechanism that may improve muscle performance and reduce pain.…”
mentioning
confidence: 99%